The Image of the ideal contemporary Filipino man a transitivity analysis of Cosmopolitan's 69 most gorgeous bachelors and ten centerfolds - Fortuno, Ma. Sheila B.; Usi, Isaac Jason M. (College of Arts and Letters, University of the Philippines Diliman, 2003)
Media has been serving us with its images of people and gender, which become the bases and representatives of the man and woman we are encouraged to become. Consequently, our concepts of masculinity and feminity are formed based on these images and representations, which often result in the stereotyping of men and women. As a result of this construction and stereotyping of gender, men have been traditionally assigned the roles of protectors of and providers for women. Men have also been characterized as "macho," physically fit, sports-minded, business-oriented, and goal-directed. They have also been characterized as insensitive and emotionally restrained, among others. These concepts, however, are said to be changing, and need to be changed, as brought about by changing economic situations and issues in gender politics. In this light, this particular study is concerned with how the current notion of masculinity is formed, specifically through language, in connection with these changes. With the use of the transitivity analysis, this study sets to determine the characteristics that make up the ideal contemporary Filipino man that derives from Cosmopolitan's 69 Most Eligible Bachelors and Centerfolds. Moreover, this resulting image of the ideal Filipino man is constructed from the perspective of women, the said text being produced mainly by women. The resulting image will then tell us whether or not the construction of masculinity and the stereotyping of men are indeed starting to change, or have changed, or on the contrary, are perpetuated instead.